Too Many Hats? The Role of Police Officers in Drug Enforcement and the Community. (18th January 2022) - Zakimi, Naomi; Greer, Alissa; Butler, Amanda
Abstract: Research on police attitudes and opinions about drugs and drug enforcement is particularly relevant amidst current critiques of policing that put their role into question. The aim of this qualitative study is to examine the role of police officers in providing public health and social support to the community and people who use drugs. Semi-structured interviews were conducted with 16 police officers working across British Columbia, Canada. Interviews were analysed thematically. We discuss two main themes: (1) the roles of police officers and (2) role strain among officers. The findings show that officers have multiple roles or wear multiple 'hats', including the crime fighter, the helper, the health responder, and the administrator. Collectively, wearing 'too many hats' caused role strain as well as tense relations with the community. Findings highlight the importance of establishing clear role definitions and expectations for police, as well as providing resources to address public health and social service needs for the community.